2018
DOI: 10.1038/s41430-018-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and behaviors regarding salt intake in Mozambique

Abstract: Most Mozambicans were aware that high salt intake can cause health problems, but the self-reported salt intake and behaviors for its control show an ample margin for improvement. This study provides evidence to guide population level salt-reducing policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
4
15
0
1
Order By: Relevance
“…For example, knowledge that salt could be detrimental for health was associated with only one salt-related practice, i.e., low discretionary use of salt. A study conducted in 2014–2015 in Mozambique also found participants high in knowledge but low in attitudes and practices, in which is similar to our study [ 25 ]. This suggests that campaigns aimed at raising awareness about the detrimental impact of salt intake on health might better translate in actual salt reduction if structural measures are also implemented, e.g., programs to reduce salt in the food served in work or school canteens and measures to limit salt intake in selected manufactured foods (e.g., bread).…”
Section: Discussionsupporting
confidence: 91%
“…For example, knowledge that salt could be detrimental for health was associated with only one salt-related practice, i.e., low discretionary use of salt. A study conducted in 2014–2015 in Mozambique also found participants high in knowledge but low in attitudes and practices, in which is similar to our study [ 25 ]. This suggests that campaigns aimed at raising awareness about the detrimental impact of salt intake on health might better translate in actual salt reduction if structural measures are also implemented, e.g., programs to reduce salt in the food served in work or school canteens and measures to limit salt intake in selected manufactured foods (e.g., bread).…”
Section: Discussionsupporting
confidence: 91%
“…This difference may be due, at least in part, to sex differences in energy intake 63 . In agreement with our results, 41,59 women have higher knowledge and healthier behaviors regarding salt intake compared with men 64‐66 . This observation may reflect more frequent engagement in health promoting practices among women, due to a greater use of health services, 67 and subsequent behavior changes to adhere to lower sodium diets compared with men.…”
Section: Discussionsupporting
confidence: 88%
“…Most participants had fairly high knowledge of the adverse health effects of excessive salt intake, regarded salt reduction as of low importance, and did not practice salt reduction behaviors. In addition, women have higher knowledge regarding salt intake than men 41,59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large variability in bread Na content observed between bakeries and the higher price of brown compared to white bread show that further improvements are possible. In Mozambique, most of the population does not adopt behaviours to reduce salt intake (32) . Among Maputo inhabitants, discretionary salt is the most frequent source of dietary Na intake (60 %) (12) .…”
Section: Discussionmentioning
confidence: 99%